PENGARUH NORMA SUBJEKTIF DAN MOTIVASI TERHADAP MINAT SERTIFIKASI AKUNTANSI - Permata, Fyana Putri; Setyorini, Christina Tri; Sudjono, Sudjono (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2019)
This is a research that have been done to 102 Accounting students in Economy and Business Faculty, Jenderal Soedirman University. Purpose of this research is to understand about accounting students’ perception on subjective norm, career, economic, social, academic title and knowledge motivation in influence of intention to take accounting certification.Accounting students (S1) in Economic and Business Faculty, Jenderal Sedirman University, who know about accounting certification – CA / CPA / CIA / CFA / others – was become the criterion in samples choosing of this research. The results of research are: (1) parents’ influence don’t become students’ consideration to take accounting certification; (2) the higer family’s influence, the higher students’ intention to take accounting certification; (3) friends’ view or suggestion didn’t affect students’ intention to take accounting certification; (4) the higher lecturers/professors’ influence, the higher students’ intention to take accounting certification; totally, subjective norm have positive and significant influence to students’ intention to take accounting certification; (5) the higher career motivation, the higher students’ intention to take accounting certification; (6) the higher economic motivation, the lower students’ intention to take accounting certification; (7) the higher social motivation, the higher students’ intention to take accounting certification; (8) academic title motivation doesn’t affect students’ intention to take accounting certification; (9) the higher knowledge motivation, the higher students’ intention to take accounting certification.